COMBINING ABILITY IN COCONUT (Cocos nucifera) - K.U.K.Nampoothiri; P.M. Kumaran; B.A. Jerard; M.J.Ratnambal E.V.V.B.Rao; V.A. Parthasarathy (International Coconut Community, 1999)
Combining ability has been proved to be a method to identify and select the parents and hybrids for increased production through the exploitation of heterosis. The exploitation of heterosis would be useful if suitable hybrids are produced for low yielding environmental conditions of littoral sandy soil. Combining ability effects for early germination, seedling girth, seedling height and breadth of laminate leaf on coconut have been reported by Louis and Chopra (1991) and on husked nut weight by Fernando (1996). Estimation of GCA and SCA variance will help to find out the gene action involved in a particular character and thus one can decide the breeding method for the improvement of the character. The present investigation was carried out to find out the general and specific combining ability effects of parents and hybrids at Central Plantation Crops Research Institute, Kasaragod.